Application of Religious Tourism Places in Province Banten, West Java - Juhriah, Een; Rahmah, Dewi Leyla (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Technological developments and the need for information lead to increasingly complex information that must be processed and presented quickly and accurately. Religious tourism is a new trend that is of interest to the public. This is evidenced by the many activities of religious managers, ranging from tour fleet providers to general public figures. The aim of the research is to produce an interactive knowledge application that can be used by the community as a method of knowledge about religious tourism in Banten Province, West Java by providing information from several religious tourist attractions accompanied by a location map. The research method used by the author is the Research and Development (R&D) method, which is a research method used to produce a particular product and test the effectiveness of the method so that it can be used to develop or validate products used in education and learning. The selection of application programs is made using the Android programming language with an easy-to-understand user interface. Based on the research results, the authors conclude that this application can be used as an effective and communicative method of knowledge for the community